2017
DOI: 10.18689/mjcrs-1000101
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction: A Comparison between Governmental and Private Out Patient Clinics in Taif, Saudi Arabia

Abstract: Objective: This study aimed to identify and compare the factors that contribute to patient satisfaction towards the medical care services between governmental and private healthcare clinics. Methods:A self-administrated (Arabic/English) questionnaire was used to conduct the all participants. Participants were selected using convenience sampling for both the governmental and private clinics.Results: Participated were 141 patients from the government clinics and 215 patients from private clinics. 75% of the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…26 The present study has been conducted in the selected primary health centers; however, there are studies which were conducted earlier to compare the satisfaction among patients in public and private hospitals. 27,28 The current study point out there is a negative impact of longer wait time on satisfaction of patients which is also acknowledged by the Institute of Medicine which recommends that the 90% of the patients should be attended within 30 minutes of their scheduled appointments. 29,30 The findings of the present study showed a statistical significance between the educational qualification and the level of significance at the health-care centers.…”
Section: Discussionmentioning
confidence: 68%
“…26 The present study has been conducted in the selected primary health centers; however, there are studies which were conducted earlier to compare the satisfaction among patients in public and private hospitals. 27,28 The current study point out there is a negative impact of longer wait time on satisfaction of patients which is also acknowledged by the Institute of Medicine which recommends that the 90% of the patients should be attended within 30 minutes of their scheduled appointments. 29,30 The findings of the present study showed a statistical significance between the educational qualification and the level of significance at the health-care centers.…”
Section: Discussionmentioning
confidence: 68%
“…23,63,64 A study in Taif found that 77% of patients who sought treatment at private healthcare facilities were satisfied with the level of care, whereas it was only 59% in the public sector. 65 The private sector in Saudi Arabia has been engaged in a range of activities related to the direct provision of healthcare services, administration and management of healthcare facilities, manufacturing of healthcare products, and financing of the healthcare systems. 66 These are carried out by various non-state actors; including national and multinational companies, non-governmental organizations, non-profit entities, and private individuals working as general practitioners and consultants in the provision of healthcare services.…”
Section: Discussionmentioning
confidence: 99%
“…Increased use of private healthcare facilities is linked to consumer dissatisfaction, various constraints and poor management practice with the public sector [18,56,57]. A study in Taif found that 77% of patients who sought treatment at private healthcare facilities were satis ed with the level of care, whereas it was only 59% in the public sector [58]. The private sector in Saudi Arabia has been engaged in a range of activities related to direct provision of healthcare services, administration and management of healthcare facilities, manufacturing of healthcare products and nancing of the healthcare systems [59].…”
Section: Discussionmentioning
confidence: 99%